The complete mitochondrial genome of the Epinephelus akaara (Perciformes: Serranidae). (3rd May 2016) - Xie, Zhenzhen; Xiao, Ling; Wang, Xiang; Tang, Lin; Tang, Zhujing; Liu, Yali; Chen, Huimin; Li, Shuisheng; Zhang, Yong; Lin, Haoran
Abstract: The complete mitochondrial genome of the Epinephelus akaara was presented in this study. The mitochondrial genome is 16, 743 bp long and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a control region. The gene order and composition of Epinephelus akaara mitochondrial genome was similar to that of most other vertebrates. The nucleotide compositions of the light strand are 27.31% of A, 16.20% of C, 28.68% of T and 27.81% of G. With the exception of the NADH dehydrogenase subunit 6 ( ND6 ) and eight tRNA genes, all other mitochondrial genes are encoded on the heavy strand.